Efektivitas Pemberian Rebusan Kunyit Asam terhadap Penurunan Disminore - Wahyu Kurnia; Rika Ruspita; Fajar Sari Tanberika; Rifa Yanti (LPPM Universitas Bhamada Slawi PSDKU D III Kebidanan Kampus Kota Pekalongan, 2026)
Perineal wounds are a common complication in Dysmenorrhea is menstrual pain commonly experienced by adolescent girls and can interfere with daily learning activities. Non-pharmacological management such as turmeric-tamarind decoction offers a safe and accessible natural alternative. This study aimed to determine the effectiveness of turmeric-tamarind decoction in reducing dysmenorrhea among Grade X students at SMAN 1 Rimba Melintang, Rokan Hilir Regency. This pre-experimental study used a one-group pretest-posttest design, conducted from December 2024 to January 2025 on 36 respondents selected through total sampling. Data were collected using a Numeric. Rating Scale (NRS) and analyzed using the Wilcoxon test. Results showed that before the intervention, most respondents experienced moderate pain (69.4%) and controlled severe pain (30.6%); after the intervention, 61.1% experienced mild pain, 25.0% moderate pain, and 13.9% reported no pain. The Wilcoxon test showed a significant decrease in pain scores (p=0.000). Turmeric-tamarind decoction is effective in reducing dysmenorrhea and may be considered a complementary therapy for adolescent girls.